Reflexión Pastoral sobre los ritos indígenas - Regan, Jaime (1971)
This issue of Allpanchis Phuturinqa has agricultural and livestock rites as its central theme. These rites represent a problem for many priests who work with the peasants. They are religious expressions different from those one finds in cities like Lima or Rome. The first missionaries in Peru suffered a tremendous shock when they found unknown religious rites, and many times they associated them with the devil. Attitudes have changed, but there is still concern about these rituals. Last year a priest asked me: "What should we do about the rites of the peasants: try to remove them or ignore them?"